2017
DOI: 10.4102/sajcd.v64i1.178
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of attitudes towards stuttering of non-stuttering preschoolers in the United States and Turkey

Abstract: Background and objectivesExtensive research documents ubiquitous negative attitudes towards stuttering, but when and how they develop is unclear. This non-experimental, comparative study examined US and Turkish preschoolers to explore the origin of stuttering attitudes cross-culturally.MethodThe authors compared stuttering attitudes of 28 US and 31 Turkish non-stuttering preschoolers on English and Turkish versions of experimental prototypes of the newly developed Public Opinion Survey on Human Attributes–Stut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
(70 reference statements)
3
15
0
1
Order By: Relevance
“…That the youngest cohort held the worst attitudes overall is not surprising. In fact, it upholds previous stuttering research which suggested cognitive and social development may explain attitudinal differences between younger and older children [16,20,22]. Differences between the youngest and oldest cohorts are particularly salient.…”
Section: Changes In Children's Stuttering Attitudessupporting
confidence: 71%
See 3 more Smart Citations
“…That the youngest cohort held the worst attitudes overall is not surprising. In fact, it upholds previous stuttering research which suggested cognitive and social development may explain attitudinal differences between younger and older children [16,20,22]. Differences between the youngest and oldest cohorts are particularly salient.…”
Section: Changes In Children's Stuttering Attitudessupporting
confidence: 71%
“…At this time, this and previous studies uphold the notion that children's stuttering attitudes improve in conjunction with their social and cognitive [16,[20][21][22]. Improvements in social awareness, perspective taking, and a more diverse social experiences might factor into children's understanding about stuttering and people who stutter, which has been posited in related research on stigma development [15].…”
Section: Limitations and Future Researchsupporting
confidence: 61%
See 2 more Smart Citations
“…Understandably, it may lead to disability (the functional communication difficulties experienced in the speaker's everyday life), impairment (the observable characteristics of the speech difficulty), and handicap (the impact of the stuttering disorder on the speaker's overall quality of life) and hence may be a cause for concern for several professionals, including family physicians, speech therapists, psychologists, and pediatricians. [123]…”
mentioning
confidence: 99%